Preliminary assessment of health risks associated with consumption of grapevines contaminated with mining effluents in Turkey: Persistent trace elements and critical raw materials - Topal, Murat; Topal, E. Isil Arslan; Obek, Erdal (Wiley, 2022)
In this study, some persistent trace elements and critical raw materials were investigated in grapevines contaminated with Pb-Zn mining effluents. The persistent trace elements under certain conditions remain without any change in form in the environment over long periods. The critical raw materials are the ones that have economic importance and have the risks associated with their supply. The health risks of persistent trace elements and critical raw materials in the leaves of grapevine that are consumed by humans were determined. The highest persistent trace elements concentrations followed the order of root > stem > leaf for Mn, Cu, Cd, Ni, and Cr while root > leaf > stem for Zn and leaf > root > stem for Pb. The maximum critical raw material concentrations for Co and V followed the order of root > stem > leaf. For Sb and La, these were leaf > root > stem and root > stem > leaf, respectively. The maximum critical raw materials concentrations for W was leaf > stem = root. The total maximum carcinogenic value was 0.146 for Cd while the total minimum carcinogenic value was 0.0054 for Pb. In this study, potential carcinogenic risk values in terms of ingestion of contaminated soil (Cr, Cd, and Ni) and dietary take of grapevine leaves (Ni, Cr, Cd, and Pb) are higher than acceptable levels (1 x 10(-4) - 1 x 10(-6)). Maximum cancer risk on human health was determined as dietary intake of grapevine leaves. When hazard quotient for dietary (HQ(die)), hazard quotient for ingestion (HQ(ing)), and hazard quotient for inhalation (HQ(inh)) values of critical raw materials were examined, the maximum values were observed for children. Also, the highest hazard quotient for dermal (HQ(der)) value was determined for men. The hazard index and total hazard index values were >1 for critical raw materials. As a result, values >1 indicated potential non-carcinogenic human health risk associated with the consumption of grapevines contaminated with mining effluents. Actual region-specific exposure estimates for consumption of grapevines, however, were not evaluated. Integr Environ Assess Manag 2021;00:1-11. (c) 2021 SETAC
Keywords: Accumulation; Contaminant; Health risk; Mining; Vine